Office 2013 All-In-One For Dummies - Weverka, Peter (Wiley, 2013)
Home and business users around the globe turn to Microsoft Office and its core applications every day. Whether you're a newcomer or a veteran Office user, this friendly-but-informative guide provides in-depth coverage on all the newest updates and enhancements to the Office 2013 suite. With an overview of tools common to all Office applications and self-contained minibooks devoted to each Office application, Office 2013 All-in-One For Dummies gets you up to speed and answers the questions you'll have down the road. Explores the new Office interface and explains how it works across the applica.
Print version record
Keywords: Microsoft Office; Business -- Computer programs; COMPUTERS; Desktop Applications; Suites; COMPUTERS; Enterprise Applications; General; Business; Computer programs